One health concept, prevalence and phenotypic antibiotic susceptibility of Escherichia coli and Salmonella isolated from meats sold in Lagos, Nigeria - Adebesin IO; Sule IO; Kolapo KT; Amoka SO; Olomoko CR; Olubunmi OH (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2023)
This study reports the one health concept, prevalence, and antimicrobial susceptibility patterns of Salmonella and Escherichia coli isolated from raw and ready-to-eat (RTE) meats sold in cities of Lagos State, Nigeria. The conventional method of isolation was used to isolate E. coli and Salmonella spp. on their respective selective media from fifty meat samples obtained from abattoirs, open display, and packaged products at various locations in the state and was confirmed by Gram's reaction and biochemical tests. Thirty-three E. coli and Twenty-seven Salmonella spp. were isolated with the overall prevalence rate recorded as 72% and 68% respectively. The isolated bacteria were subjected to antimicrobial susceptibility testing on nine different antibiotics using the agar disc diffusion method. All the Salmonella were resistant to at least one antibiotic while two E. coli isolates showed susceptibility to all the antibiotics used in this study. Of the 33 E. coli subjected to antimicrobial testing, 84.8% were susceptible to gentamicin, 81.8% susceptible to ciprofloxacin, and 75.8% susceptible to Augmentin. A lower susceptibility pattern was observed on Salmonella with 74.1% of the Salmonella being susceptible to ciprofloxacin and gentamicin, and 70.4% susceptible to azithromycin. Gentamicin was the most effective antibiotic while amoxicillin was found to be least effective against E. coli and Salmonella isolated from the meat samples used in this study. The multiple antibiotic resistance (MAR) index of Salmonella ranged between 0.11-0.67 while E. coli ranged between 0-0.89. E. coli was found to be more resistant than Salmonella and the bacteria isolated from RTE meats showed higher MAR than those isolated from raw meats.